Reflections of cultural aspects of Indian and Pakistani communities in fiction - Krčmářová, Kateřina (2006)
The thesis will trace reflections in contemporary fiction of some cultural aspects of South Asian communities living in Britain. The focus will be on the generation gap as experienced in multicultural Britain in relation to the problem of arranged or forced marriage. Hanif Kureishi's The Buddha of Suburbia and Farrukh Dhondy's short plays Romance, Romance and The Bride will serve as the primary fictional sources